PENGARUH MODEL ARIAS DISERTAI MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA SUB MATERI INVERTEBRATA DI SMA - Khofiyya, Nurlia; Ningsih, Kurnia; ., Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
This research aims to determine the influence of ARIAS (Assurance, Relevance, Interest, Assessment and Satisfaction) learning  model with mind mapping on student learning outcomes in sub material of invertebrates in class X SMAN 1 Rasau Jaya. This research was a quasy-experimental design with nonequivalent control group design. The samples of this research were class XB the experimental class and XA as the control, with a sampling technique of intact group. The instrument used was a multiple choice test with 20 questions. The average student learning outcomes in the experimental class was 14,57, while in the control group was 12,73. The result of the analysis using the U-Mann-Whitney test, obtained Zcount<-Ztable (-2,70<-1,96), meaning that there are significant differences between the learning outcomes of student taught using the learning model of ARIAS accompanied mind mapping and the learning outcomes of student taught using the conventional learning model. The effect size value obtained was 0,69 in the moderate category and giving an effect of 25,49%. Keywords: ARIAS model, mind mapping and learning outcomes.